Kontribusi Perempuan Dalam Pembaharuan Sistem Sosial di Masa Nabi Muhammad Perspektif Anthony Giddens - Suko Susilo (Asketik: Jurnal Agama dan Perubahan Sosial, 2023)
This article discusses the contribution of women to the renewal of the social system during the time of the Prophet Muhammad using Anthony Giddens' perspective. The main objective of this article is to analyze the active role of women in the social changes that occurred at that time, as well as to describe how their contributions shaped social transformation in Arab society at the time of Prophet Muhammad. The research method used is literature analysis by collecting and examining various relevant textual sources, including the Quran, Hadith, and Anthony Giddens' works on social change. This approach enabled us to gain a comprehensive understanding of the role of women in specific social and historical contexts. The results of the analysis show that women played a significant role in the process of social renewal during Prophet Muhammad. They were not only involved in religious struggles, but also contributed to various areas of life, including politics, economics, and education. Women also play an important role in supporting changes in social norms, including gender equality and the protection of women's rights. Anthony Giddens' perspective in this analysis provides a broader understanding of the role of women in social change. Concepts such as agency, social structure, and reflective action help explain how women contribute to shaping and changing the existing social systems. This study makes an important contribution to the understanding of the role of women in social history and development. Understanding the contribution of women in reforming the social system during the time of Prophet Muhammad can provide inspiration and insight for inclusive and equitable social development efforts.